Giving effective feedback : check in regularly, handle convversations, bring out the best - Thomas, James Edward (20 minute manager series., 2022)
Whether you're dealing with a problem employee or praising the good work of a colleague, you need to communicate in a way that promotes positive change in others. Giving Effective Feedback quickly walks you through the basics of delivering feedback that gets results, including: - Choosing the right time to talk - Engaging in productive dialogue - Helping both star and struggling performers - Developing a plan for effective follow-up Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly listen to and apply, for ambitious professionals and aspiring executives-from the most trusted source in business.